Strategi Pemberdayaan Masyarakat dalam Promosi Kesehatan: Sebuah Studi Literatur Mengenai Efektivitas dan Dampak Berkelanjutan - Tati Nuryati (LPPM Institut Pendidikan Nusantara Global, 2026)
Community empowerment is a core pillar of health promotion, yet ensuring its long-term sustainability remains a major field challenge. This study aims to analyze the effectiveness and sustainability of various community empowerment strategies in improving public health status. A narrative literature review was conducted using national and international peer-reviewed journals from Google Scholar and PubMed databases published between 2019 and 2024. The synthesis indicates that optimizing local peers (health cadres) and integrating cultural-religious leadership yield a 55% to 65% increase in healthy behavior adoption. Concurrently, participatory digital media interventions among urban-younger populations achieve up to a 70% success rate, although constrained by the digital divide in remote areas. Long-term sustainability hinges on shifting health workers' roles from prescriptive instructors to collaborative facilitators, thereby fostering a